Examination of regional ozone formation: POCPs for Western Australia and comparisons to other continents. (December 2015) - Lam, S.H.M.; Saunders, S.M.; Cheng, H.R.; Guo, H.
Abstract: Airshed modeling to determine photochemical ozone creation potentials (POCPs) provides a means of ranking regional emission contributions of individual volatile organic compounds (VOC) to O3 formation. Here POCPs are determined for Perth, Western Australia and compared with those from other Continents; Europe (UK), America (USA) and Asia (The Pearl River Delta and Hong Kong). Considering only the commonality of VOC across the top 50 ranked VOC by POCP and top 15 ranked VOC by POCP-weighted emission, indicates a group of 27 alkane, alkene, aromatic and oxygenated VOC that should be considered as useful targets in emission limitation and reduction strategies. This target group includes; ethene, propene, the butenes (6 VOC) and pentenes (3 VOC), trimethyl benzenes (2 VOC), xylenes (3 VOC), toluene, ethyl benzene, m-ethyl toluene, butanes (2 VOC), pentanes (2 VOC) and 2-methyl heptane, as well as methanal, ethanal and methyl-i-butyl ketone. The top 50 ranked VOC by POCP (from >130 VOC) also highlights those more reactive VOC that should be taken note of, as potential high ozone contributors, should emissions increase. Highlights: POCPs are determined for Perth, Western Australia & compared with those from other Continents. VOC are ranked by POCP & POCP-weighted emission across high and low air pollution regions. Some common VOC contributing to high O3 are identified across 4 Continents. These common VOC are a group of 27 alkane, alkene, aromatic and oxygenated compounds. Overall analysis identifies potential target VOC for further emission control studies.